Examining the Dark Tetrad: Analyzing Profiles and Their Connection to the Big Five Personality Traits. - Gómez-Leal, Raquel; Fernández-Berrocal, Pablo; Gutiérrez-Cobo, María José; Cabello-González, Rosario; Megías-Robles, Alberto (My University, 2024)
Background: The Dark Tetrad (DT) comprises the traits of Narcissism, Machiavellianism, Psychopathy, and Sadism. Previous research on the DT has typically examined these traits individually using a variable-centered approach. In this study, we take a different approach by treating the DT as a unified construct and adopting a person-centered approach. Our objective is to analyze various homogeneous subgroups of individuals characterized by specific DT profiles and explore how these profiles relate to the Big Five personality factors. Methods: To achieve this, we collected data from 1154 participants, including both men and women aged 18 to 79 years. We utilized The Short Dark Triad and the Assessment of Sadistic Personality instrument to assess DT traits and the Mini-IPIP to evaluate the Big Five personality factors. Through cluster analysis, we identified five distinct groups: Narcissism, Machiavellianism, Mean DT, Low DT, and High DT. Results: Our primary findings revealed that the High DT group exhibited higher levels of extraversion and lower levels of agreeableness and conscientiousness when compared to the Low DT group. Additionally, the Narcissism group displayed higher scores in emotional stability and openness to experience. Notably, the distribution of gender varied across the DT groups, with more men than women in the High DT group and the opposite pattern observed in the Low DT group. Conclusion: A proper understanding of personality traits is crucial for improving the evaluation and diagnostic procedures in mental health. This understanding should be based on empirical research that not only identifies these traits but also examines their interrelationships and how they interact with other variables.
Keywords: Personalidad - Trastornos; Psicopatología; Narcisismo; Sadismo; Big five; Dark Tetrad